The 5′ End of the Pea Ferredoxin-1 mRNA Mediates Rapid and Reversible Light-Directed Changes in Translation in Tobacco - Hansen, Eric R. (American Society of Plant Physiologists, 2001)
Ferredoxin-1 (Fed-1) mRNA contains an internal light response element (iLRE) that destabilizes mRNA when light-grown plants are placed in darkness. mRNAs containing this element dissociate from polyribosomes in the leaves of transgenic tobacco (Nicotiana tabacum) plants transferred to the dark for 2 d. Here, we report in vivo labeling experiments with a chloramphenicol acetyl transferase mRNA fused to the Fed-1 iLRE. Our data indicate that the Fed-1 iLRE mediates a rapid decline in translational efficiency and that iLRE-containing mRNAs dissociate from polyribosomes within 20 min after plants are transferred to darkness. Both events occur before the decline in mRNA abundance, and polyribosome association is rapidly reversible if plants are re-illuminated. These observations support a model in which Fed-1 mRNA in illuminated leaves is stabilized by its association with polyribosomes, and/or by translation. In darkness a large portion of the mRNA dissociates from polyribosomes and is subsequently degraded. We also show that a significant portion of total tobacco leaf mRNA is shifted from polyribosomal to non-polyribosomal fractions after 20 min in the dark, indicating that translation of other mRNAs is also rapidly down-regulated in response to darkness. This class includes some, but not all, cytoplasmic mRNAs encoding proteins involved in photosynthesis.